Rootstock effects on growth, reproduction and wood properties in hybrid larch (Larix x eurolepis Henry) and in some other Larix sp. grafting associations - Luc E. Pâques (Annals of Forest Science, 2025)
Abstract Key message When grafting is used in breeding, the choice of the rootstock should not be underestimated. Its impact on grafted individuals can be either beneficial for reducing tree size or enhancing flowering such as in seed orchards or detrimental if it is a source of bias in clonal testing. This is demonstrated in an experimentation with Larix where the impact of grafting on the same or a different species rootstock is studied on several traits. Context Grafting is heavily used by forest tree breeders to vegetatively propagate clones for establishment of clonal archives and seed orchards but also for clonal testing. Although of high importance in fruit trees and vines breeding, the selection of rootstocks in forest trees has drawn little attention. Aims Our objective was to test the relative impact of rootstock and scion selection with contrasted characteristics on the performance of grafted trees. Methods We performed three grafting experiments with larch (Larix sp.) combining either rootstocks and scions of the same species but with contrasted characteristics (high and low vigour and flowering capacity) or rootstocks and scions of the same and different species (homo- and hetero-plastic grafting). The performances of these combinations were monitored for over 10 years and compared for growth, wood properties, reproduction and some other traits. Results The scion strongly affected performance but, in most cases, there was no significant interaction between scion and rootstock. Rootstock effects depended on the trait under consideration and the type of grafting. The choice of rootstock had little effect on wood properties. In case of homo-grafting, some significant rootstock effects were observed for growth although these effects were much weaker than those of scion and their relative weight decreased over time, making their practical importance minor. Notably, the mean performance of the grafted trees was unaffected by the vigour of the rootstocks or by their flowering capacities. In addition, the performance of individual clones was unaffected by the choice of clonal rootstock. Rootstocks had no significant effect on reproduction, whatever their vigour or flowering capacity. Flowering abundance was maximised when using scions from heavy flowering clones. When testing for different species grafting associations, the choice of rootstock had significant effects on multiple traits: hybrid larch rootstocks outperformed Japanese larch for growth traits but the latter yielded slightly but significantly delayed flushing and superior stem straightness. Additionally, European larch rootstocks led to heavier flowering than Japanese ones. Conclusion The choice of the grafting type should be governed by breeders’ objectives. Hetero-grafting should be preferred in cases where modification of traits such as tree size or production of flowers and cones is desired, as in seed orchard management. Conversely, no positive or negative impact on traits is wanted when evaluating genotype values for purposes such as clonal testing. In such cases, homo-grafting should be preferred to limit bias due to grafting.